A Novel Pax5-Binding Regulatory Element in the Igκ Locus - Levin-Klein, Rena; Kirillov, Andrei; Rosenbluh, Chaggai; Cedar, Howard; Bergman, Yehudit (Frontiers in Immunology, 2014)
The Igκ locus undergoes a variety of different molecular processes during B cell development, including V(D)J rearrangement and somatic hypermutations, which are influenced by cis regulatory regions (RR) within the locus. The Igκ locus includes three characterized RRs termed the intronic (iEκ), 3’Eκ and Ed enhancers. We had previously noted that a region of DNA upstream of the iEκ and matrix attachment region (MAR) was necessary for demethylation of the locus in cell culture. In this study, we further characterized this region, which we have termed Dm, for demethylation element. Pre-rearranged Igκ transgenes containing a deletion of the entire Dm region, or of a Pax5 binding site within the region, fail to undergo efficient CpG demethylation in mature B cells in vivo. Furthermore, we generated mice with a deletion of the full Dm region at the endogenous Igκ locus. The most prominent phenotype of these mice is reduced somatic hypermutations in germinal center B cells in Peyer’s patches. In conclusion, we propose the Dm element as a novel Pax5-binding cis regulatory element, which works in concert with the known enhancers, and plays a role in Igκ demethylation and somatic hypermutations.